A Self-Powered and Flexible Organometallic Halide Perovskite Photodetector with Very High Detectivity - Leung, Siu-Fung (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.